Possibilidades e limites de implantação de modelos de gestão estrategica na Universidade Federal de Mato Grosso - Nunes, Jussara Luiza Figueiredo (1996)
This study aims at identifying the limits and possibilities of applying models of strategic management at the Federal University of Mato Grosso(UFMT). Using exploratory study I tried to identify the reaction of the institution and its staff to environmental changes. The theory of strategic management was used to monitor the organizational environment beginning at the identification of weak and strong points, threats and opportunities. The data was obtained through interviews with the head of the university, the heads of the administrative, academic (undergraduate and graduate) and planning areas and the directors of the colleges at the UFMT. This data was analysed qualitatively. It was possible to observe that the university's present vocation is restricted and that it must be reformulated so as to adapt itself to change. Also, there is no significant effort on the part of the institution or its staff towards giving and impulse to transformations or even perceiving the general environment. When the suggestion of a new technique to manage the university is presented, many doubts arise as to the practical results of its application for there still is a strong link with old administrative paradigms. By analysing the data obtained, my conclusion is that the factors that can limit the introduction of models of estrategic management should be diagnosed and evaluated in more depth. Future studies should search for the knowledge of the various specific aspects of these factors. However, these limits should not be considered impeditive. They should be seen as stimulators of changes when it is considered that the social objectives that justify the existence of the UFMT are larger than the relations of power and the culture of resistance to change. The unstable and turbulent environment is favorable to a change in the conventional way in which the university is managed at present; what is necessary is a decision made by the highest institutional manager to begin the processo Strategic management, as a planned management system can give flexible answers obtained from learning as well as making possible the definition of institutional growth.